Beginning of the End of Cost Competitiveness in CEE Countries – Analysis of Dependence between Labor Costs and Internationalization of the Region - Wiliński, Witold (Comparative Economic Research. Central and Eastern Europe, 2012)
The main purpose of this study is to verify whether previous low level of labor costs being one of competitive edges of CEE countries is a factor that may determine competitiveness of this region in the long run. In the study a regression analysis has been carried out on the sample of all EU countries in order to verify the dependence between internationalization degree measured by OFDI stock per capita on labor costs in manufacturing sector and on GNP per capita. The results of the regression analysis clearly show the occurrence of such dependence. This means that gradual increase in labor costs in CEE countries will result in not only reduced inflow of investments from developed countries to this region but also transfer of production to more cost competitive countries. In order to exemplify the above econometric model I carried out empirical analysis of the companies listed on the Warsaw Stock Exchange, identifying the companies for which efficiency-seeking is the main internationalization motive. The analysis of internationalization of 26 companies during the years 1990-2010 clearly shows that a significant part of investments is located outside the territory of Poland, in the countries with lower labor costs. This fact confirms that CEE countries will gradually become less and less attractive in terms of costs not only for MNEs from developed countries but also for the companies originating from transition economies.